2020
DOI: 10.1111/ceo.13708
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum and genotype‐phenotype correlation of inherited retinal dystrophy in Taiwan

Abstract: Background: Inherited retinal dystrophy (IRD) is a group of irreversible retinal degenerative disorders with significant genotypic and phenotypic heterogeneity, which cause difficulty in making a precise clinical diagnosis.Furthermore, the mutation spectrum of IRD in Taiwan remains unknown. Therefore, our study focused on investigating the spectrum of mutations among Taiwanese families with IRD using targeted exome sequencing (TES) technology. Methods: We recruited a total of 60 unrelated Taiwanese families wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Few studies have been conducted on ABCA4-associated retinal dystrophies in Taiwan. Chen et al reported that CYP4V2 and USH2A were the most common disease-causing genes in Taiwanese IRD patients, and ABCA4 in China [23,24]. However, most of the patients recruited in that study had a phenotype of RP, which may lead to selection bias in genetic epidemiology.…”
Section: Discussionmentioning
confidence: 91%
“…Few studies have been conducted on ABCA4-associated retinal dystrophies in Taiwan. Chen et al reported that CYP4V2 and USH2A were the most common disease-causing genes in Taiwanese IRD patients, and ABCA4 in China [23,24]. However, most of the patients recruited in that study had a phenotype of RP, which may lead to selection bias in genetic epidemiology.…”
Section: Discussionmentioning
confidence: 91%
“…From previous studies, EYS variants account for the largest portion of causative genes in the East Asian region, especially in Korea and Japan; EYS variants account for 20 to 30% of RP cases, and USH2A variants cause less than 10% [ 16 , 17 , 18 ]. On the other hand, USH2A variants make up 20 to 40% and EYS variants account for less than 10% of RP cases, among the total RP population in Western or European ethnicities [ 8 , 19 , 20 ] as well as Chinese or Taiwanese populations [ 7 , 21 ]. The ratios of EYS and USH2A in our study were slightly lower than those in previous studies, which shows the unique genetic characteristics of Korean patients even in comparison with those of the other East Asian nations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have not investigated the impact of copy number variation (Huang et al, 2017) and somatic mosaicism (Jin et al, 2007) in these patients. Finally, targeted exome sequencing including a panel of disease-causing genes, likewise the strategy of inherited retinal dystrophy (Huang et al, 2013(Huang et al, , 2015Xing et al, 2014;Chen et al, 2020), might be more appropriate for future genetic diagnosis of genetic HM.…”
Section: Discussionmentioning
confidence: 99%